Synthesis of Calix[4]pyrogallolarene and its Application in Spectrophotometric Determination of V(V) Metal - LOKHANDE, R.S.; S. DAPALE, SHEETAL; CHAUDHARY, A.B.; NIRUPA, S. (Asian Journal of Chemistry, 2010)
Calix[4]pyrogallolarene was synthesized and its characterization was carried out using elemental analysis, FTIR, NMR technique. The reagent was then used for the development of a new method for the extractive spectrophotometric determination of V(V) metal. The reagent forms complex with the metal to produce blue coloured complex which was then extracted into n-butanol at pH 4.2 having maxima at 600 nm. The effect of diverse anions and cations was also studied. The developed method was employed to determine V(V) metal from synthetic mixtures.